Analysis of Human Resource Readiness in Technology-Based Defense Management - Ariobimo, Muhammad; Sumarno, Ari Pitoyo; Purwantoro, Susilo Adi; Almubaroq, Hikmat Zakky (International Journal of Religion Education and Law, 2026)
The increasing adoption of digital technologies in defense organizations has fundamentally transformed defense management practices and operational models. However, the effectiveness of technology-based defense management depends not only on advanced systems but also on the readiness of human resources to operate, adapt, and sustain these technologies. This study analyzes human resource readiness within technology-based defense management by examining key dimensions such as digital competence, adaptive capability, and organizational support. Using a qualitative literature-based analytical approach, this paper synthesizes recent scholarly findings to develop a conceptual framework for assessing readiness in defense institutions. The findings indicate that insufficient human resource readiness can undermine digital transformation initiatives despite substantial technological investment. This study contributes to defense management literature by highlighting the strategic role of human capital in ensuring successful technology integration and organizational resilience.